UPAYA PENINGKATAN PENGETAHUAN MASYARAKAT MELALUI PELATIHAN PENDAFTARAN MEREK DAGANG DI NAGARI SASAK DAN NAGARI KAPA - Delfiyanti Delfiyanti; Khairani Khairani; Yasniwati Yasniwati; Wetria Fauzi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
The people of Nagari Sasak and Nagari Kapa, Sasak Ranah Pasisie District, West Pasaman Regency live from agriculture and trade. Communities trade their agricultural and plantation products from one area to another. However, the community also then processes agricultural and plantation products in the form of processed food. Furthermore, these processed foods are made in various types of food, such as processed food, which is their central mainstay and in the form of ripik and rending meat, and so on. The problem is that many people do not understand the need to register trademark rights and services for these products. The purpose of this service is to provide understanding to the public about the importance of registering registration rights and trade services so that the community is legally protected. The activity method is carried out through lectures, discussions, and training based on Law No. Law No. 20 of 2016 concerning Brands and Geographical Indications. The results of this activity then have added insight and understanding to the people of Nagari Sasak and Nagari Kapa, Sasak Ranah Pasisie District, West Pasaman Regency regarding the procedures and processes for registering trademark rights and services for the food products they make and helping to help improve the economy of the Nagari Sasak and Nagari communities Kapa.